sprains and injuries (Homoeopathy for All, 2022)
Any injury that affects the bones, muscles, ligaments, nerves, or tendons resulting in pain are considered musculoskeletal injuries. Acute pain often stems from injuries like a fall, sprain, dislocation, or a direct blow to the muscle. These injuries often occur during sports and exercise activities, but sometimes simple everyday activities can cause an injury.
Keywords: injury; musculoskeletal